2022
DOI: 10.3390/cells11111726
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytoskeletal Diaphanous-Related Formins in Hearing Loss

Abstract: Hearing relies on the proper functioning of auditory hair cells and on actin-based cytoskeletal structures. Diaphanous-related formins (DRFs) are evolutionarily conserved cytoskeletal proteins that regulate the nucleation of linear unbranched actin filaments. They play key roles during metazoan development, and they seem particularly pivotal for the correct physiology of the reproductive and auditory systems. Indeed, in Drosophila melanogaster, a single diaphanous (dia) gene is present, and mutants show steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Indeed, the hearing phenotype is inherited as a likely recessive trait in the family, and heterozygous carriers of the variant have normal hearing. This is in contrast with the mechanism of action of mutations in the other two diaphanous genes, DIAPH1 and DIAPH3 , which lead either to a gain-of-function effect or to the overexpression of the protein, respectively, and are transmitted as dominant alleles [ 4 , 10 , 12 ]. Despite the efforts to find a second NSHL family with potentially pathogenic variants in DIAPH2 , we still lack additional genetic data confirming the association of this gene with deafness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the hearing phenotype is inherited as a likely recessive trait in the family, and heterozygous carriers of the variant have normal hearing. This is in contrast with the mechanism of action of mutations in the other two diaphanous genes, DIAPH1 and DIAPH3 , which lead either to a gain-of-function effect or to the overexpression of the protein, respectively, and are transmitted as dominant alleles [ 4 , 10 , 12 ]. Despite the efforts to find a second NSHL family with potentially pathogenic variants in DIAPH2 , we still lack additional genetic data confirming the association of this gene with deafness.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several genes encoding proteins involved in the structure and function of sensory hair cells are associated with NSHL, including cytoskeletal proteins. Among these, diaphanous -related formins (DRFs) are important regulators of actin nucleation and microtubule dynamics [ 3 , 4 ]. These multi-domain proteins are active as dimers and can be functionally divided into two parts.…”
Section: Introductionmentioning
confidence: 99%
“…Formins promote the initiation and elongation of actin filaments to participate in a variety of biological processes, such as cell signaling, organ development, microtubule stabilization, cell division, and endocytosis. [12][13][14][15] Forminmediated actin assembly is regulated by a protein family consisting of formin-binding proteins (FNBPs/FBPs). Previous studies showed that the high expression of FNBP1 is closely related to the highly aggressive characteristics of tumor cells within gastric and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…They also affect actin-dependent cell signaling and gene transcription, and genomic integrity [24,25]. Not surprisingly, germline and somatic mutations perturbing formins' activity and/or expression are associated with a growing number of pathological conditions, including developmental defects of the heart, nervous system, and kidney and aging-related diseases, inherited human diseases, and cancer [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…They also affect actin-dependent cell signaling and gene transcription, and genomic integrity [24,25]. Not surprisingly, germline and somatic mutations perturbing formins' activity and/or expression are associated with a growing number of pathological conditions, including developmental defects of the heart, nervous system, and kidney and aging-related diseases, inherited human diseases, and cancer [26,27]. However, the large number of formins and the seemingly functional redundancy among certain family members make it cumbersome to attribute a given cellular function to a specific formin by means of gene knockout or knockdown approaches.…”
Section: Introductionmentioning
confidence: 99%